Entrepreneurship in cities - Mason, C. M.; Reuschke, Darja; Syrett, Stephen; Ham, Maarten van (USA Edward Elgar, 2015)
"Entrepreneurship in cities' focuses on the neglected role of the home and the residential neighbourhood context for entrepreneurship and businesses within cities. The overall objective of the book is to develop a new interdisciplinary perspective that links entrepreneurship research with neighbourhood and urban studies. A key contribution is to show that entrepreneurship in cities is more than agglomeration economies and high tech clusters. This is the first book to connect entrepreneurship with neighbourhoods and home, recognising that business activity in the city is not confined to central business districts, high streets and industrial estates but is also increasingly found in residential neighbourhoods. It highlights the importance of home-based businesses for the economy of cities. These often overlooked types of businesses and workers significantly contribute to the 'buzz' that makes cities favourable places to live and work. Including interdisciplinary and international perspectives, this will be an invaluable resource for researchers and Masters students in entrepreneurship, urban studies, geography, and planning, as well as practitioners involved in urban planning and development."--
Keywords: Entrepreneurship. -- Urban economics. -- Home-based businesses -- Economic policy. -- Economic development. -- Entrepreneurship, neighbourhood and space -- Place of neighbourhood in Entrepreneurship: attitudes, resources and sorting -- Neighbourhoods and the structure of society: implications for work and residence in the internet age -- ICT, Internet-Enabled work and implication for space and Entrepreneurship -- The re-appropriation of enterprise and urban entrepreneurialism -- Neighbourhoods, social networks and embeddedness -- Enterprising mothers in residential neighbourhoods: the role of local social capital -- Changing social networks of Entrepreneurs in Dutch residential neighbourhoods -- Ethnic Entrepreneurship: interlinking business and residential location choice -- Deprived neighbourhoods as capital for Enterprises -- Home and household -- Entrepreneurship as the business of the household -- Urban home-based businesses: How distinct are the businesses and their owners -- Mixed role of local communities in home-based economic activities in Caribbean cities -- Integrating entrepreneurship with urban and neighbourhood studies